2016
DOI: 10.1038/srep39507
|View full text |Cite
|
Sign up to set email alerts
|

Translational regulation of APOBEC3G mRNA by Vif requires its 5′UTR and contributes to restoring HIV-1 infectivity

Abstract: The essential HIV-1 viral infectivity factor (Vif) allows productive infection of non-permissive cells expressing cytidine deaminases APOBEC3G (A3G) and A3F by decreasing their cellular level, and preventing their incorporation into virions. Unlike the Vif-induced degradation of A3G, the functional role of the inhibition of A3G translation by Vif remained unclear. Here, we show that two stem-loop structures within the 5′-untranslated region of A3G mRNA are crucial for translation inhibition by Vif in cells, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 60 publications
(85 reference statements)
2
30
0
3
Order By: Relevance
“…Interestingly, it has been reported that the Vif mediated A3G inhibition is not only mediated by proteosomal degradation but also by translational repression (Stopak et al, 2003; Guerrero et al, 2016). Though it remains unclear how important each of these pathways are relative to one another in vivo , these findings suggested that both pathways could be targeted to restore cellular A3G levels.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been reported that the Vif mediated A3G inhibition is not only mediated by proteosomal degradation but also by translational repression (Stopak et al, 2003; Guerrero et al, 2016). Though it remains unclear how important each of these pathways are relative to one another in vivo , these findings suggested that both pathways could be targeted to restore cellular A3G levels.…”
Section: Discussionmentioning
confidence: 99%
“…The primer sets for this study. in the past, new host-virus relations came to be understood by through these molecules (22,23). Previously it has been reported that multiple APOBEC3 enzymes may limit the infectivity of HTLV-1 (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, by sequestering CBF-β in the E3-ubiquitin ligase complex, Vif indirectly causes a decrease in A3G transcription as the A3G gene is regulated by the RUNX transcription factor family, which requires CBF-β as cofactor ( Figure 4 C①) [ 81 ]. Degradation of A3G through the UPS has been known for a long time as the main mechanism for HIV-1 to counteract cellular restriction; however it has been shown that Vif can also inhibit A3G translation [ 82 , 112 , 113 ] and this inhibition significantly contributes to the counteraction mechanism ( Figure 4 C②) [ 82 , 112 , 113 ]. While A3G is the main member of the A3-family that efficiently restricts HIV, A3D, F and H also showed a restricting activity towards HIV-1 in the absence of Vif, even though to a lesser extent than A3G [ 114 ].…”
Section: Counteraction Of Restriction Factors By Viral Auxiliary Pmentioning
confidence: 99%